Coexisting moyamoya syndrome and type 1 diabetes mellitus: A case report and review of the literature - Bolem, Nagarjun; Nga, Vincent; Chou, Ning; Yeo, Tseng; Lin, Jeremy; Sharma, Vijay (Asian Journal of Neurosurgery, 2020)
Moyamoya disease (MMD) is an incompletely understood malady that affects many age groups, primarily in a bimodal age distribution. We present a patient with the association of type 1 diabetes mellitus (type 1 DM) and MMD followed by a review of the existing literature. We found five papers that describe this association, in the form of one case report, one case series, and three retrospective reviews. Despite a poor understanding of the underlying pathophysiology, a clear association between autoimmune conditions and MMD appears to exist. Clinicians who manage such patients ought to be vigilant and have a high index of suspicion when young patients with type 1 DM present with new onset of neurological symptoms.
Keywords: Chorea; external carotid–internal carotid bypass; hemiballismus; moyamoya disease; type 1 diabetes mellitus